Analisis Faktor Penyebab Terjadinya Miopia pada Mahasiswa Fisika Angkatan 2020 Universitas Negeri Padang - Yuliati, Netri; Atifah, Yusni (AHKAM, 2024)
The organ of sight plays a central role in acquiring necessary information, enabling us to carry out various daily activities normally. The eyes can experience refractive errors, one of which is nearsightedness or myopia. Myopia is a refractive eye disorder with a high prevalence worldwide. There are various factors that can influence the development of myopia. One highly influential factor is the habit of reading and writing at too close a distance. Additionally, other factors include a history of exposure to light from computers or gadgets, age, type of pregnancy, birth history, nutritional status, deficiency of vitamins A and D, as well as genetic factors or family history. This study aims to determine the factors causing myopia among physics students of the 2020 intake at Padang State University. This research employs a descriptive qualitative research method and was conducted in December 2023. Research findings show that the highest percentage of individuals unaware of distant objects' presence is 70%, while 20% are aware, and 10% occasionally notice distant objects. The highest percentage of smartphone usage duration is 100%, with usage exceeding 5 hours, while 0% use it for less than 5 hours. Regarding smartphone lighting, 50% prefer bright illumination, 30% opt for moderate brightness, and 20% prefer dim lighting.